Improved prediction of solvation free energies by machine-learning polarizable continuum solvation model - Amin Alibakhshi (Nature Portfolio, 2021)
Accurate theoretical evaluation of solvation free energy is challenging. Here the authors introduce a machine-learning based polarizable continuum solvation approach to improve the accuracy of widely accepted continuum solvation models by almost one order of magnitude without additional computational costs.